The stability of partnerships across the transition from education to employment - Heintz-Martin, Valerie [Verfasser]; Zabel, Cordula [Verfasser] (My University, 2019)
"This article examines the dynamics of emerging adults' partnerships across the school-to-work transition. While previous research studied the impact of the school-to-work transition on cohabitation entry only, we focus on partnership disruption, accounting for cohabitation as a parallel process. We examine whether partnership volatility is tied to enrolment in education, which would imply greater opportunities for relationship and identity exploration, but also postponed family formation, for those enrolled in education longer. Moreover, we study the impact of non-employment after education on the stability of early partnerships. The analyses are based on PAIRFAM, a survey on relationship dynamics for young cohorts in Germany. Focusing on western Germany, we study partnerships that began during education. In a three-process model, we examine partnership disruptions and transformations of non-cohabiting partnerships into cohabitations, comparing the impact of educational enrolment, employment, and non-employment while controlling for selectivity in entering employment. We find that young men's transition from education to employment stabilizes their partnerships. However, partnership instability is higher for young men with phases of non-employment after education than for those who are employed. In contrast to men, the school-to-work transition has no effect on partnership stability for women." (authors' abstract; BIBB-Doku)

"Viele junge Paare fiebern dem Berufseinstieg entgegen, um endlich ein unabhängiges Leben zu zweit beginnen zu können. Doch tatsächlich wird diese Zeit des Umbruchs für manche Partnerschaften zur Belastungsprobe. Vor allem bei jungen Männern, denen der Berufseinstieg misslingt, ist die Trennungsrate deutlich erhöht." Das ist das zentrale Ergebnis einer repräsentativen Studie. Sie untersucht, inwiefern sich der Übergang von der Ausbildung in den Beruf stabilisierend oder destabilisierend auf Partnerschaften auswirkt. (Herausgeber; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; P 1.1 Jugendliche; I 2.1.2 Alte Bundesländer; Berufseinmündung; Zweite Schwelle; Jugendlicher; Junger Erwachsener; Arbeitslosigkeit; Partnerschaft; Einflussfaktor; Geschlechtsspezifische Faktoren; Westdeutschland